FEM optimization of process parameters and in-process cooling in the friction stir processing of magnesium alloy AZ31b - Ammouri, A.H. (2017)
Controlling the temperature in friction stir processing (FSP) of Magnesium alloy AZ31b is crucial given its low melting point and surface deformability. A numerical FEM study is presented in this paper where a thermo-mechanical-based model is used for optimizing the process parameters, including active in-process cooling, in FSP. This model is simulated using a solid mechanics FEM solver capable of analyzing the three dimensional flow and of estimating the state variables associated with materials processing. Such processing (input) parameters of the FSP as spindle rotational speed, travel speed, and cooling rate are optimized to minimize the heat affected zone, while maintaining reasonable travel speeds and producing uniformity of the desired grain size distribution of the microstructure in the stirred zone. The simulation results predict that such optimized parameters will result in submicron grain sized structure in the stirred zone and at the corresponding stirred surface. These simulation predictions were verified using published experimental data.